Genetic Landscape of Somatic Mutations in a Large Cohort of Sporadic Medullary Thyroid Carcinomas Studied by Next-Generation Targeted Sequencing - Ciampi, Raffaele (iScience, 2019)
Sporadic Medullary Thyroid Carcinoma (sMTC) is a rare but aggressive thyroid tumor. RET and RAS genes are present in about 50%–80% of cases, but most of the remaining cases are still orphan of a genetic driver. We studied the largest series of sMTC by deep sequencing to define the mutational landscape. With this methodology we greatly reduced the number of RET- or RAS-negative cases and we confirmed the central role of RET and RAS mutations. Moreover, we highlighted the bad prognostic role of RET mutations in sMTC and consolidated the favorable prognostic role of RAS mutations. For the first time, we showed that the variant allele frequency represents an additional prognostic marker inside the group of RET-mutated sMTC.